Effect of tofacitinib therapy on angiotensin converting enzyme activity in rheumatoid arthritis - Kacsándi, Dorottya; Fagyas, Miklós; Horváth, Ágnes; Végh, Edit; Pusztai, Anita; Czókolyová, Monika; Soós, Boglárka; Szabó, Attila Ádám; Hamar, Attila; Pethő, Zsófia; Bodnár, Nóra; Kerekes, György; et al. (Frontiers in Medicine, 2023)
Introduction The Renin-Angiotensin-Aldosterone system (RAAS) has been implicated in the regulation of the cardiovascular system and linked to rheumatoid arthritis (RA). Little information has become available on the effects of Janus kinase (JAK) inhibition on RAAS. Here we studied the effects of 12-month tofacitinib treatment on angiotensin converting enzyme (ACE), ACE2 production and ACE/ACE2 ratios in RA along with numerous other biomarkers. Patients and methods Thirty RA patients were treated with tofacitinib in this prospective study. Serum ACE concentrations were assessed by ELISA. ACE2 activity was determined by a specific quenched fluorescent substrate. ACE/ACE2 ratios were calculated. We also determined common carotid intima-media thickness (ccIMT), brachial artery flow-mediated vasodilation (FMD) and carotid-femoral pulse-wave velocity (cfPWV) by ultrasound. C-reactive protein (CRP), rheumatoid factor (RF) and anti-citrullinated protein autoantibodies (ACPA) were also determined. All measurements were performed at baseline, as well as after 6 and 12 months of tofacitinib treatment. Results After the dropout of 4 patients, 26 completed the study. Tofacitinib treatment increased ACE levels after 6 and 12 months, while ACE2 activity only transiently increased at 6 months. The ACE/ACE2 ratio increased after 1 year of therapy (p < 0.05). Logistic regression analyses identified correlations between ACE, ACE2 or ACE/ACE2 ratios and RF at various time points. Baseline disease duration also correlated with erythrocyte sedimentation rate (ESR) (p < 0.05). One-year changes of ACE or ACE2 were determined by tofacitinib treatment plus ACPA or RF, respectively (p < 0.05). Conclusion JAK inhibition increases serum ACE and ACE/ACE2 ratio in RA. Baseline inflammation (ESR), disease duration and ACPA, as well as RF levels at various time points can be coupled to the regulation of ACE/ACE2 ratio. The effect of tofacitinib on RAAS provides a plausible explanation for the cardiovascular effects of JAK inhibition in RA.